Dressing the naked hand : the world's greatest guide to making, staging, and performing with puppets - White, Amy, 1966-; Pulham, Mark H., 1955-; Blankenship, Dallin, 1986- (Sanger, CA : Familius, 2015)
"This ultimate puppetry guide includes: how to make pupets from stuffed animals, how to guild your own hand pupet, how to create advanced Muppet-like puppets using master techniques, how to build simple, intermediate, and advanced puppet stages, how to bring your puppet to life with convincing body language, voices, diction, and emotions"--Front cover flap.
A letter to the reader -- A history lesson -- Part I. Creating the masterpiece : Chapter one. Stuffet puppet workshop ; Chapter two. Hand puppet laboratory ; Chapter three. Advanced puppet workshop ; Chapter four. Building the stage -- Part II. Acting lessons : Chapter 5. Body language & emotion ; Chapter six. Vocal lessons ; Chapter seven. Dress rehersal -- Resources.
"Includes a DVD with over 2 hours of hilarious how-to videos"--Cover.
System requirements for accompanying videodisc: DVD player or DVD-ROM drive.
Keywords: Puppets; Puppet making; Puppet theaters; Puppet theater; Puppets; Puppet making